BLACK GRAM LEAF MEAL AS A REPLACER OF DE-OILED RICE BRAN IN THE DIET OF LABEO ROHITA (HAMILTON, 1822) FINGERLING - JAISWAL, SHATRUPA; KUMAR, SHIVENDRA; NAYAK, SUJIT KUMAR; MOGALEKAR, H. S.; BANIK, ADITI (Journal of the Inland Fisheries Society of India, 2026)
Black Gram leaf meal (BGLM) underwent assessment through a 60-day feeding experiment within the diet of Labeo rohita fingerlings. Six iso-nitrogenous (30% CP) and isocaloric (360 Kcal/100 g) diets, namely Control i.e., T1 (0% BGLM, 30% DORB); T2 (3% BGLM, 27% DORB); T3 (6% BGLM, 24% DORB); T4 (9% BGLM, 21% DORB); T5 (12% BGLM, 18% DORB); T6 (15% BGLM, 15% DORB) were formulated. A total of one hundred and eighty acclimated fish (14.16 ± 0.16g) were randomly assigned into six treatment groups in triplicate, with a stocking density of 10 fish per tank, and were fed the respective diets at satiation levels. The incorporation of black gram leaf meal (BGLM) at levels up to 9% exhibited no impact on the growth rate of Labeo rohita fingerlings in comparison to the control (0%), however, the inclusion of BGLM at either 12% or 15% notably reduced the growth rate. Among the different groups, T6 displayed a noteworthy decrease (P< 0.05) in nutrient utilization compared to the other experimental groups. Additionally,  significantly higher (P< 0.05) HSI and GSI values were observed in the T6 group when compared with the control and  other treatment groups. The comprehensive findings indicated that BGLM can be effectively integrated up to 9% by substituting DORB without compromising growth, thus suggesting its potential as an alternative component in the diet of Labeo rohita fingerlings.